Circulating high-molecular-weight RAGE ligands activate pathways implicated in the development of diabetic nephropathy - Penfold, Sally A.; Coughlan, Melinda T.; Patel, Sheila K.; Srivastava, Piyush M.; Sourris, Karly C.; Steer, David; Webster, Diane E.; Thomas, Merlin C.; MacIsaac, Richard J.; Jerums, George; Burrell, Louise M.; Cooper, Mark E.; et al. (Kidney international, 2010)
The accumulation of advanced glycation end products is thought to be a key factor in the initiation and progression of diabetic nephropathy. Here we determined whether the size of the ligands for the receptor for advanced glycation end products (RAGEs) that were present in the serum of patients with type 2 diabetes modulates their pathogenic potential. Serum was collected from control subjects and patients with type 2 diabetes with varying degrees of renal disease (normo-, micro-, or macroalbuminuria). The titers of the RAGE ligands N-carboxymethyllysine (CML), S100A, S100B, and high-mobility group box 1 (HMGB1) were measured by enzyme-linked immunosorbent assay in serum as well as in pooled size-fractionated serum. We also measured cellular binding of serum fractions to mesangial cells transfected with RAGE and examined the downstream signaling pathways. Circulating CML was increased in patients with type 2 diabetes, whereas HMGB1 was decreased. S100A8, S100BA9, and soluble RAGE were unchanged. The high-molecular-weight (over 50kDa) serum fraction contained the greatest proportion of RAGE ligands, with all immunoreactivity and cellular binding observed only with serum fractions over 30kDa. High-molecular-weight serum from macroalbuminuric patients showed greater RAGE binding capacity, modulation of cell-surface RAGE expression, increased phospho-protein kinase C-α, and p65 nuclear factor κB DNA-binding activity, which were competitively inhibited by soluble RAGE or CML neutralizing antibodies. These data show that ligands that activate RAGE present in the circulation of patients with type 2 diabetes and nephropathy are predominantly of high molecular weight.